Low-temperature oxidation characteristics and reaction pathways of crude oil within tight shale during air injection - Shuai Zhao; Wanfen Pu; Yibo Li; Qi Jiang (Petroleum)
The investigation of low-temperature oxidation (LTO) of crude oil within tight shale holds significant importance due to its implications for subsequent oxidation reactions and enhanced oil recovery in the process of air injection. In this study, the tight shale sample underwent oxidation at various LTO temperatures, followed by an analysis of the resulting gas composition. Furthermore, the oxidized oil was separated from the tight shale and subjected to characterization using electron paramagnetic resonance, nuclear magnetic resonance, and negative ion electrospray Fourier transform-ion cyclotron resonance mass spectrometry techniques. The primary focus was on examining the distinct LTO reaction pathways observable across different temperature ranges. The findings demonstrated a correlation between LTO temperature and the concentration of free radicals, which predominantly resided on aromatic hydrocarbons, alkanes, and oxygen atoms. Additionally, the proton count of polycyclic aromatic hydrocarbons exhibited a continuous increase from 83 to 350°C, suggesting intensified aromatization and condensation reactions involving aliphatic and aromatic compounds. With rising LTO temperature, the molecular structure of O2 compounds underwent significant transformations, characterized by increased condensation degree and a decrease in low carbon number molecular structures, while higher equivalent double bonds and carbon number molecular structures became more prevalent. The LTO reaction pathways of shale oil included cycle paths 1, 2, and 3. The influence of cycle path 1 diminished at temperatures ranging from 83 to 150°C and 250 to 350°C, whereas the significance of cycle paths 2 and 3 increased, resulting in an overall escalation of the oxidation rate with temperature elevation. It was observed that the shale oil LTO process exhibited a negative temperature coefficient within the temperature range of 150 to 250°C, emphasizing the criticality of overcoming the energy barrier in this region to achieve stable combustion. This comprehensive investigation provides valuable insights into the mechanisms underlying LTO in crude oil confined within tight shale.